2019
DOI: 10.3329/kyamcj.v10i2.42783
|View full text |Cite
|
Sign up to set email alerts
|

Study On Outcome of Different Combination of Dexamethasone, Hyaluronidase and Placental Extract for Treatment of Oral Submucous Fibrosis

Abstract: Background:Oral submucous fibrosis is a chronic debilitating disease of the oral cavity characterized by inflammation and progressive fibrosis of the submucosal tissues. It is a precancerous condition of the oral mucosa characterized by excessive production of collagen leading to inelasticity of the oral mucosa and atrophic changes of the epithelium. A wide range of treatment including drug management, surgical therapy, and physiotherapy have been attempted till date, with varying degrees of benefit, but none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…Similar studies have shown significant improvement in trismus and burning sensation with the use of dexamethasone plus hyaluronidase combination, indicating the efficacy of this drug regimen Hasan et al 20 The consumption of Gutka and Chalia emerged as the most frequent causes of OSF in our study, consistent with earlier research by Patil et al 18 Notably, all patients exhibited restricted mouth openings with visualized and palpable fibrous bands on the buccal mucosa. Over the 6-month follow-up period after the regimen, mouth opening considerably increased in both groups, aligning with findings reported by Bhambal and colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies have shown significant improvement in trismus and burning sensation with the use of dexamethasone plus hyaluronidase combination, indicating the efficacy of this drug regimen Hasan et al 20 The consumption of Gutka and Chalia emerged as the most frequent causes of OSF in our study, consistent with earlier research by Patil et al 18 Notably, all patients exhibited restricted mouth openings with visualized and palpable fibrous bands on the buccal mucosa. Over the 6-month follow-up period after the regimen, mouth opening considerably increased in both groups, aligning with findings reported by Bhambal and colleagues.…”
Section: Discussionsupporting
confidence: 90%